Inhibitory effects of compounds from Zingiberaceae species on platelet activating factor receptor binding - Jantan, Ibrahim; Pisar, Mazura; Mohd. Sirat, Hasnah; Basar, Norazah; Jamil, Shajarahtunnur; Mat Ali, Rasadah; Jalil, Juriyati (John Wiley & Sons, Ltd, 2004)
Ten compounds isolated from Alpinia mutica Roxb., Curcuma xanthorrhiza Roxb. and Kaempferia rotunda Linn. (Family: Zingiberaceae) were investigated for their platelet-activating factor (PAF) antagonistic activities on rabbit platelets using 3H-PAF as a ligand. Among them, four compounds showed significant inhibitory effects. Alpinetin and 5,6-dehydrokawain isolated from A. mutica exhibited IC50 values of 41.6 and 59.3 µm, respectively. The IC50 values of 3-deacetylcrotepoxide and 2-hydroxy-4,4,6-trimethoxychalcone from K. rotunda were 45.6 and 57.4 µM, respectively. 1-Methoxy-2-methyl-5-(1,5-dimethylhex-4-enyl)-benzene, synthesized by methylation of xanthorrhizol which was obtained from C. xanthorrhiza, showed an IC50 value of 40.9 µm. The results indicated that these compounds were relatively strong PAF receptor binding inhibitors